Identification of thaumatin‐like protein and aspartyl protease as new major allergens in lettuce (Lactuca sativa). Issue 12 (25th August 2013) - Muñoz‐García, Esther; Luengo‐Sánchez, Olga; Haroun‐Díaz, Elisa; Maroto, Aroa Sanz; Palacín, Arancha; Díaz –Perales, Araceli; de, Manuel; Labrador‐Horrillo, Moisés; Vivanco, Fernando; Cuesta‐Herranz, Javier; Pastor‐Vargas, Carlos
<x xml:space="preserve">Abstract</x> Scope Today, about 2–8% of the population of Western countries exhibits some type of food allergy whose impact ranges from localized symptoms confined to the oral mucosa to severe anaphylactic reactions. Consumed worldwide, lettuce is a Compositae family vegetable that can elicit allergic reactions. To date, however, only one lipid transfer protein has been described in allergic reaction to lettuce. The aim of this study was to identify potential new allergens involved in lettuce allergy. Methods and results Sera from 42 Spanish lettuce‐allergic patients were obtained from patients recruited at the outpatient clinic. IgE‐binding proteins were detected by SDS‐PAGE and immunoblotting. Molecular characterization of IgE‐binding bands was performed by MS. Thaumatin was purified using the Agilent 3100 OFFGEL system. The IgE‐binding bands recognized in the sera of more than 50% of patients were identified as lipid transfer protein (9 kDa), a thaumatin‐like protein (26 kDa), and an aspartyl protease (35 and 45 kDa). ELISA inhibition studies were performed to confirm the IgE reactivity of the purified allergen. Conclusion Two new major lettuce allergens—a thaumatin‐like protein and an aspartyl protease—have been identified and characterized. These allergens may be used to improve both diagnosis and treatment of lettuce‐allergic patients.